Cdc14: a highly conserved family of phosphatases with non-conserved functions? - Mocciaro, Annamaria; Schiebel, Elmar (Journal of cell science, 2010)
CDC14 was originally identified by L. Hartwell in his famous screen for genes that regulate the budding yeast cell cycle. Subsequent work showed that Cdc14 belongs to a family of highly conserved dual-specificity phosphatases that are present in a wide range of organisms from yeast to human. Human CDC14B is even able to fulfill the essential functions of budding yeast Cdc14. In budding yeast, Cdc14 counteracts the activity of cyclin dependent kinase (Cdk1) at the end of mitosis and thus has important roles in the regulation of anaphase, mitotic exit and cytokinesis. On the basis of the functional conservation of other cell-cycle genes it seemed obvious to assume that Cdc14 phosphatases also have roles in late mitosis in mammalian cells and regulate similar targets to those found in yeast. However, analysis of the human Cdc14 proteins (CDC14A, CDC14B and CDC14C) by overexpression or by depletion using small interfering RNA (siRNA) has suggested functions that are quite different from those of ScCdc14. Recent studies in avian and human somatic cell lines in which the gene encoding either Cdc14A or Cdc14B had been deleted, have shown - surprisingly - that neither of the two phosphatases on its own is essential for viability, cell-cycle progression and checkpoint control. In this Commentary, we critically review the available data on the functions of yeast and vertebrate Cdc14 phosphatases, and discuss whether they indeed share common functions as generally assumed.
Gesehen am 27.04.2023